Creativity and innovation in Islam: It's necessity in Islamic education - Sulaiman A.; Mohd Zarif M.M.; Mohd Nizah M.A.; Atoma P.; Ismail A.; Kandil H.M.T.E. (Medwell Journals, 2024)
Indexed by Scopus